Integrasi Nilai Islami dalam Kurikulum Merdeka Pendidikan Anak Usia Dini Berbasis Kemandirian - Anisza, Anisza; Wanati, Wanati; Fajriani, Kartika (Educational Consultant & Counseling Career (EC3) Mataram, 2026)
This study explores the integration of Islamic values in the Merdeka Curriculum for early childhood education (PAUD) to foster children’s independence. Although numerous studies have discussed character education and independence in early childhood, research specifically examining the systematic integration of Islamic values of independence within the flexible framework of Kurikulum Merdeka remains limited. Most existing literature focuses on general teaching methods or environmental factors, while deeper exploration of how Islamic values can be naturally embedded to strengthen moral and practical independence is still needed. This research aims to analyze the forms, strategies, and relevance of integrating Islamic independence values in PAUD Kurikulum Merdeka implementation and how this integration supports the formation of independent character in young learners. Using a qualitative narrative literature review approach, data were collected from reputable journals, books, national policy documents, and previous studies, then analyzed descriptively through data reduction, thematic grouping, interpretation, and conclusion drawing. The study highlights that Islamic values such as ikhtiar, amanah, discipline, and responsibility can be effectively internalized through daily routines, play-based learning, educator modeling, and project activities rather than as separate subjects. The findings imply that an integrative value-based curriculum can nurture independence not only as a practical skill but also as a moral disposition. This approach offers practical guidance for PAUD teachers and policymakers in developing more holistic and culturally relevant curricula, while contributing theoretically to the field of Islamic character education in early childhood.